2014
DOI: 10.1002/hbm.22517
|View full text |Cite
|
Sign up to set email alerts
|

Distinct fine‐scale fMRI activation patterns of contra‐ and ipsilateral somatosensory areas 3b and 1 in humans

Abstract: Inter-areal and ipsilateral cortical responses to tactile stimulation have not been well described in humans S1 cortex. By taking advantage of high signal-to-noise ratio at 7 T, we quantified blood oxygenation level dependent (BOLD) response patterns and time courses to tactile stimuli on individual distal finger pads at a fine spatial scale, and examined whether there are inter-areal (area 3b versus area 1) and inter-hemispheric response differences to unilateral tactile stimulation in healthy human subjects.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 81 publications
4
32
0
Order By: Relevance
“…Figure 3a shows the averaged (n = 20) activation maps for the index (red) and middle (water blue) fingers. In consistent with the previous studies (Ann Stringer et al, 2014;Martuzzi et al, 2014), we found that the middle finger was localized to a more superior position than index finger.…”
Section: Somatotopic Mapping For Right Index and Middle Fingerssupporting
confidence: 93%
“…Figure 3a shows the averaged (n = 20) activation maps for the index (red) and middle (water blue) fingers. In consistent with the previous studies (Ann Stringer et al, 2014;Martuzzi et al, 2014), we found that the middle finger was localized to a more superior position than index finger.…”
Section: Somatotopic Mapping For Right Index and Middle Fingerssupporting
confidence: 93%
“…Peripheral nerve injury can enhance activity in ipsilateral S1 (Fornander et al, 2016), especially at the level of interneurons in laminae V and VI (Pelled et al, 2009). Crucially, ipsilateral activations and deactivations in S1 are diffused and not somatotopically specific (Helmich et al, 2005; Reed et al, 2011; Ann Stringer et al, 2014; Geva et al, 2017). They can modulate the amplitude of the S1 response (which is not of interest here), but there is no evidence that they affect the spatial (somatotopic) organisation of the contralateral responses (Reed et al, 2011; Ann Stringer et al, 2014; Geva et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Crucially, ipsilateral activations and deactivations in S1 are diffused and not somatotopically specific (Helmich et al, 2005; Reed et al, 2011; Ann Stringer et al, 2014; Geva et al, 2017). They can modulate the amplitude of the S1 response (which is not of interest here), but there is no evidence that they affect the spatial (somatotopic) organisation of the contralateral responses (Reed et al, 2011; Ann Stringer et al, 2014; Geva et al, 2017). This is further confirmed by our preliminary imaging data, in which we found that unilateral vs. bilateral fingertip mapping yielded both greatly similar and highly reproducible fingertip maps in S1 (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…Although the role of ipsilateral M1 in motor control is not fully understood, it has been proposed that unilateral movements produce temporary inhibition of ipsilateral M1, which is thought to restrict motor output to the hemisphere contralateral to the intended movement (Beaule et al, 2012;Buetefisch et al, 2014;Chiou et al, 2013;Kobayashi et al, 2003). Unilateral tactile stimulation also produces facilitation and inhibition in contralateral and ipsilateral somatosensory areas (Stringer et al, 2014). Interestingly, a poorer motor performance in healthy adults during unimanual tasks is associated with less suppression of ipsilateral sensorimotor activation (McGregor et al, 2013).…”
Section: Functional Connectivity In Prhdmentioning
confidence: 99%